2019
DOI: 10.1039/c9sm01224a
|View full text |Cite
|
Sign up to set email alerts
|

Bubbles nucleating on superhydrophobic micropillar arrays under flow

Abstract: When a supersaturated aqueous solution flows over a microstructured, hydrophobic surface, bubbles tend to nucleate. Here, we control heterogeneous nucleation of gas bubbles from supersaturated CO2 solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…4). Further, it has been reported that flow increases the rate of growth of nanobubbles on superhydrophobic surfaces 53,54 . On LIS, higher flow rates increase the portions of exposed areas of the Teflon substrate to the water and, therefore, we expect that higher flow also increases nucleation site density.…”
Section: Resultsmentioning
confidence: 98%
“…4). Further, it has been reported that flow increases the rate of growth of nanobubbles on superhydrophobic surfaces 53,54 . On LIS, higher flow rates increase the portions of exposed areas of the Teflon substrate to the water and, therefore, we expect that higher flow also increases nucleation site density.…”
Section: Resultsmentioning
confidence: 98%
“…For the surface of square cylinder microstructure, the total shear stress and pressure drop energy will be greatly affected by staggered and aligned arrangement, but not for triangular microstructure. Bat et al [76] studied the effect of cylinder shape on gas nucleation in saturated aqueous solution (Figure 3a,b). It was found that the shape and arrangement of hydrophobic microcolumns have an effect on bubble nucleation, and the flow direction also affects bubble nucleation.…”
Section: Layout and Shape Of The Microstructuresmentioning
confidence: 99%
“…Reproduced with permission. [76] Copyright 2019, Royal Society of Chemistry. c) The longitudinal microgrooves of SHS.…”
Section: Layout and Shape Of The Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, fine‐tuning of buoyant forces and even neutral buoyancy could be achieved by controlling bubble nucleation in submerged devices. [ 63 ] This approach includes electrowetting, [ 64 ] electrocatalysis, [ 65 ] acoustic waves, [ 26 ] heating (plasmonic local heating or overall heating), [ 66 ] nucleation from a supersaturated solution [ 67 ] and others. In the context of miniature robotics, this becomes even more challenging as fuel may not be possible to integrate into a small scale system and will deplete over time.…”
Section: Diving Swimming and Buoyancy Regulationmentioning
confidence: 99%